Poverty among social and economic groups in India in 1990s - Sundaram, K.; Tendulkar, Suresh D. (2003)
This paper examines the levels and changes in poverty indicators of the rural and urban population in India disaggregated by social and economic groups. The analysis is based on the comparable estimates of poverty for the mixed reference period computed from the unit record data for the 50th (1993-94) and the 55th (1999-2000) rounds of the Consumer Expenditure Surveys conducted by the National Sample Survey Organisation. The issue is how far different social and economic groups shared the overall decline in poverty in the 1990s. The social groups most vulnerable to poverty have been identified to be scheduled caste and scheduled tribe households with both these groups having above average levels of poverty indicators in their respective population segments. In terms of changes in poverty in the 1990s, it is found that while scheduled caste, agricultural labour (rural) and casual labour (urban) households experienced declines in poverty on par with the total population, scheduled tribe households fared badly in both the segments. - Reproduced.
Keywords: Poverty - India; Poverty